Energy harvesting device based on a metallic glass/PVDF magnetoelectric laminated composite - Lasheras, A. (2015)
A flexible and low cost energy harvester device based on the magnetoelectric (ME) effect has been designed using Fe64Co17Si7B12 as amorphous magnetostrictive ribbons and PVDF as the piezoelectric element. Sandwich-type laminated composite of 3 cm long has been fabricated by gluing these ribbons to the PVDF with the Devcon 5 minute epoxy. Good power output and power density of 6.4 μW and 1.5 mW/cm3, respectively, have been obtained through a multiplier circuit. All values have been measured at the magnetomechanical resonance of the laminate. The effect of the length of the ME laminate on the power output has been also studied, exhibiting a decay as the length of the ME laminate does. Nevertheless, good performance of such device has been obtained for a 0.5 cm long device, working already at 337 KHz, within the low radio frequency (LRF) range.